Digital Transformation in Mutual Fund Distribution: Assessing the Role of Robo-Advisory Platforms for Sustainable Growth in India - Zahiruddin Babar, Rishi Prakash Shukla (Journal of Informatics Education and Research, 2024)
The Indian mutual fund industry is going through a phase of extensive digital transformation and the development of robo-advisory platforms appear to be one of the key aspects of this change. The automation capabilities of these platforms, as well as their cost-effectiveness and scalability, allow distributors to improve the efficiency of their operations and provide better client service. Nonetheless, digitalization adoption is slowed down by technological obstacles, customer reluctance, and high initial costs (in particular for small-scale distributors). Abstract : This paper investigates the effects of robo-advisory platforms on real business sustainability by exploring whether and how robo-advisory platforms affect operational cost, client acquisition, and portfolio management. The study identifies critical digital adoption enablers and barriers through a survey of AMFI-registered mutual fund distributors. Results show that a combination of human advisory ability and AI-based automation prove to be the optimal long-term solution. This can be achieved through digital literacy programs, the personalization capabilities of AI, regulatory nudges, and a responsible blend of the traditional and digital advisory models (that is, using the strengths of both) to achieve a sustainable development path for mutual fund distribution. Future research needs to focus on investor behavior in adopting a digital investing and an AI-driven advisory framework.